Avaliação do grau de autogestão dos empreendimentos econômicos solidários: elaboração de um modelo de análise - Costa, Lucelia Borges da (2010)
The solidary economy is a different way to get work and income for people are excluded from labor market. However, many enterprises of solidary economy do not work because of deficiencies in the practice of self-management. This study aims to propose a model to analyze the self-management. Here, it is presented as a process where there are five degrees / types of self-management. The model was based on bibliographic review and experiences in advising cooperatives. The development of the model included a case study, which allowed adjust it, and the construction of scenarios which enabled a better understanding of the limits and possibilities of it.